Rs-198 Liquid Biofertilizers Affect Microbial Community Diversity and Enzyme Activities and Promote Vitis vinifera L. Growth. (19th June 2020) - Lu, Huadan; Wu, Zhansheng; Wang, Wenfei; Xu, Xiaolin; Liu, Xiaochen
Abstract : Chemical fertilizers were applied on perennial tree vines to obtain high yields, which have resulted in considerable deterioration of soil quality, and it is likely to have negative impacts on the development of the grape industry. In this study, P. putida Rs-198 liquid biofertilizer (Rs198LBF) was inoculated into grape rhizosphere soils to assess its influence on grape growth and microbial community. Field experiment results showed that grape growth and quality increased depending on the concentrations of Rs198LBF applications. The berry weight, length, and width in addition with 60 ml Rs198LBF (1.44 × 10 13 cfu m l − 1 Rs-198) per grapevine treatment (BFP3) were 17.2%, 6.2%, and 4.4% higher than those of CK (control, non-inoculation) treatment, respectively. The available phosphorus contents in addition with 40 ml Rs198LBF per grapevine (BFP2) and BFP3 treatments were 12.6% and 55.3% higher than those of CK treatment (P < 0.05 ). The activities of invertase and alkaline phosphatase were improved in BFP2 and BFP3 treatment compared with those in CK. The relative abundance of potentially beneficial bacteria significantly increased compared with that in CK treatment (P < 0.05 ). The clusters of orthologous groups (COG) annotation illustrated that the application of 60 ml Rs198LBF increased the relative abundance of metabolic genes in rhizosphere soil. The results of this study show that biofertilizer is very effective in enhancing plant growth and affects soil community diversity.